Analysis of Economic Opportunities and Challenges in Sumedang Regency - Nurjanah, Adjeng (Decision, 2023)
This article examines the economic landscape of Sumedang Regency, West Java, Indonesia, identifying key opportunities for growth and the significant challenges that need to be addressed for sustainable development. Utilizing a descriptive analytical approach based on secondary data and regional economic indicators, this study explores the potential of various sectors and the obstacles hindering their progress. The findings highlight both promising avenues for economic expansion and critical issues requiring strategic intervention to ensure the prosperity of Sumedang Regency